2017
DOI: 10.1186/s12877-017-0467-7
|View full text |Cite
|
Sign up to set email alerts
|

Exergames versus self-regulated exercises with instruction leaflets to improve adherence during geriatric rehabilitation: a randomized controlled trial

Abstract: BackgroundImproving mobility in elderly persons is a primary goal in geriatric rehabilitation. Self-regulated exercises with instruction leaflets are used to increase training volume but adherence is often low. Exergames may improve adherence. This study therefore compared exergames with self-regulated exercise using instruction leaflets. The primary outcome was adherence. Secondary outcomes were enjoyment, motivation and balance during walking.MethodsDesign: single center parallel group non-blinded randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 23 publications
3
51
0
2
Order By: Relevance
“…For this reason, it is important to take away the fear of new technologies in this vulnerable group if they are to use a VR exergame. Oesch et al [29] showed in their study that self-regulated exercise using instruction lea ets were superior to exergames regarding adherence in a geriatric inpatient rehabilitation setting.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is important to take away the fear of new technologies in this vulnerable group if they are to use a VR exergame. Oesch et al [29] showed in their study that self-regulated exercise using instruction lea ets were superior to exergames regarding adherence in a geriatric inpatient rehabilitation setting.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is important to take away the fear of new technologies in this vulnerable group if they are to use a VR exergame. Oesch et al [29] showed in their study that selfregulated exercise using instruction leaflets were superior to exergames regarding adherence in a geriatric inpatient rehabilitation setting. However, this study was not tested with a VR system but with a Microsoft Kinect exergame, through the effect of immersion this result should be tested with a VR system, because different effects could occur.…”
Section: Discussionmentioning
confidence: 99%
“…Only five studies evaluated health and well-being related outcomes (81)(82)(83)(84)(85). Studies tended to limit to measuring product usability and end-user satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the Cochrane risk of bias assessment are presented in Figure 2. High performance and detection bias were identified in two trials (81) (84), high reporting bias in one trial (81) and high allocation concealment bias in one trial (84).…”
Section: Risk Of Bias Summarymentioning
confidence: 99%
See 1 more Smart Citation